Planting strawberries in the home garden - Dmytryk, A. O. (ТДАТУ, 2019)
The best time for planting strawberry is from late April to mid-May. During this period, there is still no heat, but there is already a lot of sunlight. In autumn the most appropriate time is between late August and until mid-September, thus the seedlings have enough time for acclimatization and put down a good root system.
Keywords: strawberrie; growing method; open ground